Ref: Ferreira Pedrosa et al. More Training, Less Trainability: True? A muscle Swelling Analysis (doi: 10.32098/mltj.03.2024.03) - Vinnycius Nunes de Oliveira (Muscles, Ligaments and Tendons Journal, 2024)
.